Integrative and Complementary Therapies in Primary Health Care: a way to humanize care - Mariana Cabral Schveitzer; Marcos Venicio Esper; Maria Júlia Paes da Silva (O Mundo da Saúde)
This study aimed to identify how the incorporation of complementary and integrative practices in Primary Health Care has helped to promote the humanization of care. We developed a systematic literature survey using the descriptors ‘Atenção Primária em Saúde’ (Primary Health Care) and ‘Práticas Integrativas e Complementares’ (Complementary Therapies) and the connector AND in the following databases: PubMed and EMBASE, looking for articles published until 2011. A total of 1434 references were found, and 680 of these were selected by title and 15 by abstract. The ideal to include CAM in the APS is to think within the logic of humanized care, and to do this we must consider: to promote research on CAM, to insert CAM in undergraduate courses and in health professionals training, to promote international collaboration, to promote the meeting between traditional healers and health care practitioners, and the organization of a list of herbal and medicinal plants recommended by health systems.